MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS DENGAN METODE EKSPLORASI - Nenden Mutiara Sari (AlphaMath : Journal of Mathematics Education, 2015)
This research is a experimental research. The aim of this study was to determine whether the mathematical problem solving ability of students who get learning with exploration method is better than the students who get expository. The population of this study was all students of class VIII SMP in Cimahi. Sampling studies selected by strata. The first step is to choose a school in the town of Cimahi random, then choose two classes at the school by random. The instrument used in this study include the test instrument and the instrument of non tests. Test instruments used in the form of an evaluation sheet consisted of pretest and posttest, whereas the non-test instrument used was the questionnaire. Analysis is conducted quantitative data analysis. The results showed that the mathematical problem solving ability of students who received learning by exploration method is better than the mathematical problem solving ability of students who received expository. Keywords: exploration methods, mathematical problem-solving ability, expository method